Syncope as a presenting feature of complete extrusion of a unipolar permanent pacemaker - Cinosh Mathew; Rajneesh Calton (Wolters Kluwer Medknow Publications, 2016)
Complete extrusion of a permanent pacemaker is an extremely rare complication. We report a unique case of a patient presenting with syncopal episodes after complete extrusion of his implanted pacemaker. An 82-year-old gentleman with a history of pacemaker implantation, 6 years back, presented with syncopal episodes and was found to have complete extrusion of his pacemaker out of its pocket. An electrocardiography revealed complete heart block which would revert to paced rhythm when the pulse generator would be pushed back into the pacemaker pocket. Neglecting the pre-extrusion stage, he presented with syncopal episodes after complete extrusion and loss of contact of the unipolar pacemaker with the pacemaker pocket resulting in complete loss of pacing.